2022
DOI: 10.3390/foods11172703
|View full text |Cite
|
Sign up to set email alerts
|

Food and Gut Microbiota-Derived Metabolites in Nonalcoholic Fatty Liver Disease

Abstract: Diet and lifestyle are crucial factors that influence the susceptibility of humans to nonalcoholic fatty liver disease (NAFLD). Personalized diet patterns chronically affect the composition and activity of microbiota in the human gut; consequently, nutrition-related dysbiosis exacerbates NAFLD via the gut–liver axis. Recent advances in diagnostic technology for gut microbes and microbiota-derived metabolites have led to advances in the diagnosis, treatment, and prognosis of NAFLD. Microbiota-derived metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 154 publications
0
2
0
Order By: Relevance
“…Several studies have reported the composition MASH, as it shows strong positive correlations with the metabolites deoxycholic acid, D-pinitol, choline, raffinose, and stachyose (25) . The latter two metabolites include glucose and fructose, both sugars that have been associated with increased inflammation and liver fibrosis in patients with MASLD in excess (25,27) . In addition, the increase in Bacteroides promotes a decrease in fecal short-chain fatty acids and amino acids, which are products of bacterial fermentation of carbohydrates associated with various beneficial effects on the organism and may be detrimental to MASLD (25,26,28) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the composition MASH, as it shows strong positive correlations with the metabolites deoxycholic acid, D-pinitol, choline, raffinose, and stachyose (25) . The latter two metabolites include glucose and fructose, both sugars that have been associated with increased inflammation and liver fibrosis in patients with MASLD in excess (25,27) . In addition, the increase in Bacteroides promotes a decrease in fecal short-chain fatty acids and amino acids, which are products of bacterial fermentation of carbohydrates associated with various beneficial effects on the organism and may be detrimental to MASLD (25,26,28) .…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of intestinal microbiota composition have repeatedly been discussed to be associated with impairments of intestinal barrier function and an increased translocation of PAMPs like bacterial endotoxin [ 75 ]. Furthermore, results of studies in rats and mice suggest that a chronic intake of fructose-rich diets either feeding fructose alone or in combination with a high-fat diet is associated with marked changes in the relative abundance of several bacterial families and species in feces [ 76 , 77 ]. Specifically, results of several studies suggest that a chronic intake of a fructose-rich chow or drinking solution results in a decrease in Bifidobacterium and Lactobacillus in feces of rats [ 78 , 79 ].…”
Section: Fructose Intestinal Microbiota and Intestinal Barriermentioning
confidence: 99%